Development and refinement of the interview protocol: interview questions for international school teacher retention - Leong, Sok Yee; Said, Hamdan (International Journal of Evaluation and Research in Education (IJERE), 2024)
For novice researchers, creating a list of interview questions as part of the interview procedure to collect data for addressing the research questions is always a challenge. Despite several studies have provided vital suggestions for novice researchers in developing and refining interview questions, few studies offer a clear path for designing and improving interview questions. The suggested guidelines from past research lack empirical evidence, particularly in the field of education. This study aimed to present the process of developing and refining an interview protocol used in an international school teacher retention study. This study suggested and tested five phases in the development and refinement of a qualitative interview protocol: i) establishing preliminary questions based on a literature review; ii) ensuring alignment of interview questions with research questions; iii) constructing an inquiry-based conversation; iv) receiving feedback on interview protocols; and v) piloting the interview protocols. It provides comprehensive and user-friendly guidance for novice researchers in developing qualitative instruments. Using this roadmap can help novice researchers to prepare for the interview process, remain open to new findings and enhance the effectiveness of qualitative interview tools.